SURVEY OF ETHNOMEDICINAL PLANTS USED BY BHIL COMMUNITY FROM SELECTED VILLAGES OF SANTRAMPUR TALUKA, MAHISAGAR DISTRICT, GUJARATA (International Association of Biologicals and Computational Digest, 2023)
Ethno-botanical research on medicinal plants was conducted in selected villages of Santrampur taluka, Mahisagar district, Gujarat. The main aim of this study was collating the data of ethno-medicinal plants which is used by tribal communities in selected area. This study was focuses on identifying the medicinal plants, collections of their data, disease treated, preparation method, used plants parts which is used in traditional medicine and etc. It was also focuses on the traditional knowledge of indigenous people. The data was collected through personal interviews and questionnaires by the tribal people of selected areas. It s also present a list and uses of medicinal plants. This study provides information about the 15 ethno-medicinal plants belonging to 15 families, which is used by indigenous people in their traditional and various diseases.
Keywords: Ethno- botanical, Ethno medicinal, Santrampur taluka, traditional medicine